APLIKASI UJI SKRINING FITOKIMIA TERHADAP DAUN UNCARIA TOMENTOSA SEBAGAI BAHAN UTAMA DALAM PEMBUATAN TEH - Iskandar, Dodi (JURNAL TEKNOLOGI TECHNOSCIENTIA, 2020)
Uncaria Tomentosa plants grow around Pontianak and peat forests in West Kalimantan. The leaves of it turned out to have a high selling value, even some were exported abroad. The benefits of Uncaria Tomentosa leaves are as an ingredient in making herbal tea. This leaf has efficacy as a remedy for sore bronchitis, sore throat, water fat, tumors, asthma, and clamydia or sexually transmitted diseases, especially in young women. Departing from this, there needs to be publications that reveal scientifically about this plant. So that by knowing the content of compounds that are in the leaves can break the community to be able to process it from raw material into pure material so that it hopes will increase the sale value even higher. But to go there, of course, must first start from basic research. The content of chemical compounds in plants is called phytochemicals. This Plant has chemical compounds source that can be used as medicine. The method used in this research is experimentation in the laboratory. Using phytochemical screening tests following Novindriana, et. al. (2013) procedure. The result is that the ethanol extract of Uncaria Tomentosa leaves contains alkaloid, flavonoid, polyphenol, triterpenoid, steroid, saponin, and tanin compounds.